Density‐dependent effects of eastern Kamchatka pink salmon (Oncorhynchus gorbuscha) and Japanese chum salmon (O. keta) on age‐specific growth of western Alaska chum salmon. (7th October 2020) - Frost, Tessa J.; Yasumiishi, Ellen M.; Agler, Beverly A.; Adkison, Milo D.; McPhee, Megan V.
Abstract: Hatcheries release >4.5 billion juvenile Pacific salmon ( Oncorhynchus spp.) into the North Pacific Ocean annually, raising concerns about competition with wild salmon populations. We used retrospective scale analysis to investigate how the growth of chum salmon ( O . keta ) from western Alaska is affected by the abundance of chum salmon from Japanese hatcheries and wild pink salmon ( O . gorbuscha ) from the Russian Far East. Over nearly five decades, the growth of Kuskokwim River chum salmon was negatively correlated with the abundance of Japanese hatchery chum salmon after accounting for the effects of sex and spring/summer sea‐surface temperature in the Bering Sea. An effect of wild eastern Kamchatka pink salmon abundance on the growth of Kuskokwim River salmon was detectable but modest compared to the intraspecific competitive effect. A decrease in Japanese hatchery chum salmon releases in 2011–2013 was not associated with increased growth of Bering Sea chum salmon. However, the abundance of wild chum salmon from the Russian Far East increased during that time, possibly obscuring reduced competition with hatchery chum salmon. Our results support previous evidence that chum salmon are affected by intraspecific competition, and to a lesser extent interspecific competition, in the North Pacific, underscoring that the effects of salmon hatchery production transcend national boundaries.